Comparison of Friedrich Holderlin and John Keats in their respective backgrounds with emphasis on the differences between their two countries - Guder, Gotthard (The University of Edinburgh, 1942)
There are, as my Bibliography shows, many works on Hölderlin and Keats considered individually, so that any new work that claims, like the present thesis, to be independent, needs some. justification.

The questions arise: Is there any sense in comparing these two poets? What is the essence of Hölderlin and the essence of Keats?

It may be simply stated that both John Keats and Friedrich Hölderlin were great poets. The first glimpse we take of them shows us two, men living and writing at about the same time, often on similar themes; both with an actual poetic life of a very few years, both with personal histories of a sad and tragic nature. Sharing in some of the characteristics of the Romantic age, they were not necessarily wholly Romantic themselves. Both claimed for themselves the right to challenge authority, and as original genúpses to strike out on a path for themselves.

My task is to explain and compare the characteristic individualities of these poets, by considering their respective backgrounds. The literature of the past, I think, we can only truly understand, if we can relate it to the history, not only of the political movements, but also of the religious, philosophical and scientific movements of the time.

The particular purpose of this investigation is to ascertain and bring out the differences between Germany and England at that period, and to consider how these two poets, with certain basic similarities in temperament and gifts, developed differently in their different environments. The individualistic point of view lays emphasis on the importance of self- realisation; on the other hand, the environmental point of view makes primary and fundamental questions such as the value of knowledge or social duties and responsibilities. By 'environment' I imply more than "surroundings which compass an individual", namely, the "specific continuity of the surroundings with his own active tendencies."

Both poets have seen most deeply into the meaning of Nature; both brought to their study and the individual interpretation peculiar to each, the supreme qualities of close and loving observation and sympathy. And both poets 'resemble each other in the determination which their genius gave to these qualities.

Both poets were deeply conscious that poetry was their mission; it is revealed in their writings, and we have their own words for it too. Poetry as Hölderlin saw it was entrusted with the mission of revealing to a community the gods it should serve. Poetry sums up the circumstances in which a people comes into communion with its gods and in such poetry finds its higher life expressed and realised at one and the same time. Keats's conviction of the poet's office is to be the voice of one proclaiming a message, making clear a vision, transmuting into the words of a less esoteric language the conception and enunciation of a high truth, so that it may be "understanded of the people ". The function of the poet is to draw away the veils that obscure the splendours of Nature, and reveal their true and intrinsic beauty to man, so that in poetry he may find comfort to soothe him when laden with cares, and raise his thoughts above everyday life.

In Part I it is the differences between the two backgrounds, especially in so far as they arise from deep -seated differences between the two countries and peoples, on which particular stress is laid. It may be a fact, as Dr. Johnson says, that "Nobody can write the life of a man but those who have eat and drunk and lived in social intercourse with him." Unfortunately such a requirement cannot now be fulfilled in the case of Hölderlin and Keats, but we can at least get to know much that was said and done by those who did come into close personal contact with them. So, too, we can contemplate their external circumstances of every kind and so form some idea of the effects these may have had on what they wrote.

During my preparations it became clear to me that such an attempt requires more to carry it through than the sharp clearness of critical reasoning. That is necessary. But it is more necessary to have a psychological and emotional sympathy.

In Part II, therefore, I have endeavoured in this way to trace the growth and development of the soul from its initial stages, with the influences which have been brought to bear on it.

I attempt to show to what degree Hölderlin and. Keats resemble each other, and how far what was most similar in them came to be differently expressed, Partly because of their backgrounds and partly because of their different psychologies.